Pendekatan Lean Manufacturing Menggunakan Metode VALSAT Untuk Mengidentifikasi Waste Pada Produksi Kontruksi Baja (Studi Kasus Di PT. Ometraco Arya Samanta) - Inge Ventarani Abdul; Farizi Rachman; Bayu Wiro Karuniawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2024)
PT. Ometraco Arya Samanta which is engaged in steel manufacturing and civil engineering that produces project buildings. The company found a waste problem that occurred in the production process so that there was a delay in product delivery. In this problem, waste was found in the production process, the causes and alternative improvements that can increase the efficiency of the production process. This causes an inefficient production process, so by reducing waste it can increase production efficiency and company performance and productivity. Analysis of the Lean Manufacturing approach using the Value Stream Mapping (VSM) and Value Stream Analysis Tools (VALSAT) methods can help identify waste, analyze the causes of waste, and provide proposals in minimizing waste occurrence. The results of the calculation on process activity mapping with a result of 104.4, supply chain response matrix with a result of 55.5, production variety funnel with a result of 16.8, quality filter mapping with a result of 23, demand amplification mapping with a result of 35.1, decision point analysis with a result of 23.6, physical structure with a result of 23.4. From the results of the questionnaire distribution, the lowest results were obtained by waste environmental health and safety and waste over production and the highest results were obtained by waste motion, transportation, waste waiting. The main cause of waste is because the distance between the previous process and the next process takes a lot of time to move it, occurs because the material in the warehouse has run out and the delivery from the supplier is late, so workers are waiting for material confirmation. It is rare for sudden orders to customers in the middle of the production process that are not in accordance with the purchasing order (PO), causing the effect of delays.